STAFFING MECHANISM TRIPLE HELIX - L. Artamonova (Publishing House of the State University of Management, 2016)
The article discusses the problems of organization of scientific and production activities with the aim of import substitution as a systemic problem of the national economy. The authors believe that the most appropriate theoretical basis is the mechanism of the triple helix, with some adaptation to modern conditions. This tool can make only with qualified personnel, who must be prepared according to the “dual education”. Recommendations for the integrated management of human capital development.